جودة التعليم العالي ومتطلبات التنمية البشرية - أحمد, زقاوة (Sciences de l'Homme et de la Société, 2013)
تتناول الدراسة الحالية موضوع الجودة الشاملة في التعليم العالي، الذي أصبح أسلوبا حديثا في التسيير البيداغوجي وتفعيل الأداء البشري. كما يسلط الضوء على علاقة المؤسسة الجامعية بالتنمية الاقتصادية والاجتماعية من خلال تحديد متطلبات سوق العمل من مؤهلات ومهارات عملية. تعتمد الدراسة المنهج الوصفي التحليلي، الذي يقوم على توظيف أدبيات التنمية والجودة الشاملة والدراسات السابقة وتحليلها قصد توظيفها في الإجابة عن تساؤلات الدراسة. وخلصت الدراسة الى أن التنمية تتأثر ايجابا بنوعية التعليم ومدى قدرته على الاستجابة لمتطلبات سوق العمل.    The article examines the issue of global quality in high education which has recently become a method in teaching management and human performance activation. It also highlights the relationship between the university and socio-economic development through the identification of labor market requirements of  qualifications and practical skills. The study is based on the descriptive and analytical approach which emphasizes on the literarature of development and  global quality, and on previous studies so as to answer the questions related to the study. In the end, the study reached the conclusion that development is positively influenced by the quality of education and also by its ability to respond to labor market’s needs.